Thirteen new Costa Rican species belonging to the genus Triraphis Ruthe (Braconidae: Rogadinae) with their host records - Valerio, Alejandro A.; Shaw, Scott R. (Zootaxa, 2015)
Thirteen new species belonging to the genus Triraphis Ruthe are described and illustrated: Triraphis baios sp. nov., T. balteus sp. nov., T. chinusi sp. nov., T. cortazari sp. nov., T. defectus sp. nov., T. guarusa sp. nov., T. huidobroi sp. nov., T. ikelosops sp. nov., T. melasops sp. nov., T. paraholos sp. nov., T. proxilus sp. nov., T. simphlex sp. nov. and T. willei sp. nov. The lepidopteran hosts were feeding on 17 genera of plants within 16 families. Two families of Lepidoptera are reported as new hosts for Triraphis: Acraga sp. (Dalceridae) parasitized by T. paraholos sp. nov. and Norape sp. (Megalopygidae) by T. guarusa sp. nov. Moreover, four Triraphis species are treated as new combinations under the genus Triraphis sensu van Achterberg: Triraphis areatus (Cresson) comb. n., T. fasciipennis (Cresson) comb. n., T. fusciceps (Cresson) comb. n. and T. ornatus (Cresson) comb. n..